From Ghrita to Microemulsion: Innovative Delivery of Medhya Rasayana for Neuroprotection - Deore, Sharada Laxman; Vighne, Ram Chhatrapati; Baviskar, Bhushan Arun (International Journal of Pharmaceutical Investigation, 2026)
Background The aim of the current investigation is to develop a microemulsion of bioactive enriched fractions of Indian traditional medicinal plants Bacopa monnieri and Centella asiatica to enhance neuroprotective efficacy overcoming drawbacks of traditional formulations. Materials and Methods Microemulsion comprising bioactive enriched fractions of Bacopa monnieri and Centella asiatica are prepared, characterized and evaluated for its neuroprotective and neurocognitive efficacy as well as potency by in vitro antioxidant, anti-cholinesterase, anti-inflammatory activities. Particle size, polydispersity index, viscosity, zeta potential, electrical conductivity, drug content, pH measurement, percentage transmittance, FTIR and DSC analysis found promising and demonstrated that the integrity of the microemulsion. Results and Discussion The optimized microemulsion formula exhibited chemical and physical stability during study duration. DSC and FTIR studies confirmed compatibility of excipients and bioactive enriched fractions. Values of electrical conductivity 0.0743 mS/cm, 0.0746 mS/cm, and 0.0745 mS/cm for BM, CA and mix combinations of microemulsions respectively. Oil in water type microemulsion confirmed in staining tests of optimized microemulsion formula. Conclusion Microemulsions of bioactive-enriched fractions Bacopa monnieri and Centella asiatica are next-generation delivery systems that help in overcoming solubility, stability, and bioavailability challenges of herbal actives, making them more clinically relevant.
Keywords: Centella; Bacopa; Asiaticosides; Bacosides; Acetylcholinesterase